TRIB1 and TRPS1 Gene Polymorphisms Are Associated with the Incidence of Acute Coronary Syndrome and Plasma Lipid Concentrations - Gilberto Vargas-Alarcón; Óscar Pérez-Méndez; Rosalinda Posadas-Sánchez; Héctor González-Pacheco; Teresa Juárez-Cedillo; Galileo Escobedo; Victoria López-Olmos; José Manuel Fragoso (Biology, 2025)
In recent years, data from genome-wide association studies (GWAS) have shown that the genes coding for transcriptional repressor GATA binding 1 (TRPS1) and tribbles pseudokinase 1 (TRIB1) play an important role in plasma lipid profiles and act as risk factors for coronary heart disease (CHD). The aim of this work was to explore whether single nucleotide polymorphisms (SNPs) in the TRSP1 (rs231150 and rs2737229) and TRIB1 (rs2980880 and rs2954029) genes are involved in acute coronary syndrome (ACS) and plasma lipid levels. We included 1262 patients diagnosed with ACS and 1051 controls. According to inheritance models, the minor alleles of the SNPs (rs2737229 A, rs2980880 C, and rs2954029 T) were associated with an increased incidence of ACS (p < 0.05). In a sub-analysis that included only the control subjects, the same minor allele frequency was associated with increased total cholesterol, HDL-cholesterol, and LDL-cholesterol levels and low triglyceride levels. In conclusion, rs2737229, rs2980880, and rs2954029 polymorphisms are associated with a risk of developing ACS and with elevated plasma lipid levels. Our results suggest that the TRSP1 and TRIB1 are implicated in the incidence of ACS through of increased of plasma lipid profile.